1999
DOI: 10.1042/bj3390055
|View full text |Cite
|
Sign up to set email alerts
|

Conserved polar residues in the transmembrane domain of the human tachykinin NK2 receptor: functional roles and structural implications

Abstract: We have studied the effects of agonist and antagonist binding, agonist-induced activation and agonist-induced desensitization of the human tachykinin NK2 receptor mutated at polar residues Asn-51 [in transmembrane helix 1 (TM1)], Asp-79 (TM2) and Asn-303 (TM7), which are highly conserved in the transmembrane domain in the rhodopsin family of G-protein-coupled receptors. Wild-type and mutant receptors were expressed in both COS-1 cells and Xenopus oocytes. The results show that the N51D mutation results in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…5s-59 For example, the thyrotropin-releasing hormone receptor was completely inactivated by mutation to a non-H-bonding residue at the position of Asp83 or at both positions of Asn55 and Asn302.55-In several receptors an Asp-Asn pair at positions of Asp83 and Asn302 was required for activation of G proteins, but their positions can be interchanged without loss of this activity. [57][58][59] The examples suggest that different H-bonding interactions of these residues are required for stabilising the dark state and for attaining the activated state.…”
Section: Transmembrane Domainmentioning
confidence: 98%
“…5s-59 For example, the thyrotropin-releasing hormone receptor was completely inactivated by mutation to a non-H-bonding residue at the position of Asp83 or at both positions of Asn55 and Asn302.55-In several receptors an Asp-Asn pair at positions of Asp83 and Asn302 was required for activation of G proteins, but their positions can be interchanged without loss of this activity. [57][58][59] The examples suggest that different H-bonding interactions of these residues are required for stabilising the dark state and for attaining the activated state.…”
Section: Transmembrane Domainmentioning
confidence: 98%
“…Sampling was started from the reference point of DT 2 ¼ 0°, DT 7 ¼ 0°(the rhodopsin configuration) and covered most of the points on the grid of DT 2 from )20°to 40°and DT 7 from )20°to 20°. Totally, [25][26][27][28][29][30] configurations of the TM bundle were subjected to energy minimization.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…This was supported by the fact that amino acids corresponding to Asp74 and Asn298 are naturally reversed in some mammalian receptors of the GnRH-R. Interestingly, while reciprocal mutation of these residues partially restored GnRH binding in the mouse GnRH-R (32), no restoration was observed in the same mutants of the rat GnRH-R (33). Subsequent studies suggested the existence of a more extended hydrogen bond network between the conserved residues that correspond to Asn46, Asp74, Asn298, and Tyr302 in the AT 1 receptor in the mouse thyrotropinreleasing hormone receptor (31) and the human tachykinin NK 2 receptor (29). A recent study on the human thyrotropin receptor (51) described a system of interactions between the two residues that involves residues in TM6 and the internal water molecules.…”
Section: Significance Of Interaction Between the Conserved Asp And Asmentioning
confidence: 99%
“…In this study, we also hypothesized that one aspect of receptor activation involves concerted rotations of various TM helices along their long axes. This hypothesis was based on experimental results of numerous site‐directed mutagenesis studies in many GPCRs that were interpreted as indications of TM rotations relative to the ground state structures 30–42. For instance, a recent example of this type of study presented evidence for possible rotation of TM5 in the constitutively active mutant of the angiotensin receptor type 1 43.…”
Section: Introductionmentioning
confidence: 99%